2011
DOI: 10.1111/j.1365-2141.2011.08788.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in advanced stage T‐cell lymphoblastic lymphoma of children and adolescents: a report from Japanese Paediatric Leukaemia/Lymphoma Study Group (JPLSG) and review of the literature

Abstract: Summary T‐cell acute lymphoblastic leukaemia (T‐ALL) and T‐cell lymphoblastic lymphoma (T‐LBL) are combined into one category as T lymphoblastic leukaemia/lymphoma in the current World Health Organization (WHO) classification. However, there is still ongoing discussion on whether T‐ALL and T‐LBL are two separate entities or represent two variant phenotypes of the same disease. Cytogenetic analysis has been used to identify the molecular background of haematological malignancies. To compare the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…The outcome with the hyper-CVAD regimen in LBL was first reported by Thomas et al [2], while Sekimizu et al reported that among their patients, 30 (91%) achieved CR, and 3 (9%) achieved PR [5]. But it appears that in our study patients treated with the hyper-CVAD regimen had a poorer prognosis, which may be explained by the too small sample size.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The outcome with the hyper-CVAD regimen in LBL was first reported by Thomas et al [2], while Sekimizu et al reported that among their patients, 30 (91%) achieved CR, and 3 (9%) achieved PR [5]. But it appears that in our study patients treated with the hyper-CVAD regimen had a poorer prognosis, which may be explained by the too small sample size.…”
Section: Discussionmentioning
confidence: 48%
“…Cytogenetic abnormalities show no prognostic value in adult, though they are related to an aggressive clinic course. No chromosomal or molecular abnormalities have been consistently shown to carry prognostic significance except t (9;17) (q34;3), which is associated with an aggressive clinical course in children [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…About 56-69% abnormal karyotypes, with 3-5% hyperdiploid, 25-44% pseudodiploid and 22-25% hyperdiploid were shown in both T-LBL and T-ALL [38].…”
Section: T Lymphoblastic Lymphomamentioning
confidence: 96%
“…Many of the oncogenes associated with T-ALL, such as NOTCHI, ABL1, SET and NUP214 also exists in 9q34. Thus, it is reasonable that translocation involving 9q34 are more common in T-ALL than T-LBL [38]. The gene FBXW7 is closely related to NOTCHI mutation.…”
Section: Translocation Of the T-cell Receptor (Tcr) Loci Exists In Bomentioning
confidence: 99%
“…HOX11 is aberrantly expressed in childhood T-ALL as a result of either two chromosomal translocations, t(7;10)(q35;q24) and t(10;14)(q24;q11) which place the HOX11 coding sequence under the transcription control of T-cell receptor regulatory elements. HOX11L2 is involved in a cryptic translocation, t(5;14)(q35;q32), detected only by FISH resulting in its ectopic transcription (10,14) . The aim of this study was to determine the prognostic value of two structurally related homeobox genes TLX1/HOX11 and TLX3/HOX11L2 on the clinical outcome of T-ALL patients.…”
Section: Introductionmentioning
confidence: 99%